Structural Design and Motion Analysis of the Wearable Knee Joint Exoskeleton - Li Jing; Zhou Jianjun; Zhao Yiqin; Wen Zhiye (Jixie chuandong)
The mechanical exoskeleton is a kind of new electromechanical device that imitates the biological exoskeleton. A wearable flexible knee joint exoskeleton is designed,and the kinematics and dynamics analysis of the lower limb is carried out through using the human body 5 bar simplified model. The angle change curve of the knee joint is consistent with the CGA database through the Matlab/Simulink simulation and the correctness of mathematical model is verified. The lower limb exoskeleton can walk normally through the dynamic simulation of ADAMS,the correctness of the driving function of the knee joint is verified and the torque curve of knee joint is prepared for the control. Finally,the physical prototype is developed and the rationality of the exoskeleton is proved through the angle change curve of the knee joint in the contrast experiment of wear or not-wear exoskeleton.